Living on the Edge: Young People, Social Work and Climate Policy and Action - Dominelli, Lena (Indonesian Social Work Consortium (ISWC), 2024)
Today’s young people will be on the frontline of experiencing the worst effects of the climate crisis as they age in a world in which climate-induced disasters will be increasing in intensity and frequency unless ‘net zero’ is reached before the current deadline of 2050. The case for urgently addressing the climate crisis by 2030 has been made by the Intergovernmental Panel on Climate Change (IPCC) since the Paris Agreement in 2015. Years later, and with the disappointing outcomes of the 2021 United Nations Convention on Climate Change (UNFCCC) Conference of the Parties (COP) 26 meeting in Glasgow, Scotland and COP27 in Sharm el-Sheik, Egypt in 2022, little has changed. Politicians fill the airwaves with fine words about reaching ‘net zero’. Meanwhile, countries like India, the 3rd largest polluter do not aim to meet ‘net zero’ until 2070! Young people have limited engagement in formal policy-making locally, nationally, and globally, so their voices remain largely ignored. Practitioners, seldom engage young people in climate action. This professional disinterest in young people’s experiences of the climate crisis and aspirations for a net zero future must end. This article focuses on young people’s voices, research and action, including their involvement in COP26 activities in Glasgow. Young people, as agentic persons, can make decisions about climate change, and are well-placed to do this if given the opportunity. Social workers can support and mobilise young people in climate action and demand that climate change be included in the social work curriculum.